Identifying objective behavioural measures of expert driver situation awareness. (December 2021) - McKerral, Angus; Pammer, Kristen
Highlights: The present study frames expert and non-expert drivers' situation awareness (SA) within the Perceptual Cycle Model. SA is assessed along with driver gaze behaviour to correlate behavioural and verbal report measures. Both verbal counts and fixation-related gaze are found to reliably differentiate expert and non-expert drivers. Differences in expert and non-expert gaze behaviour informs an understanding of expert SA. Abstract: Efforts to reduce road crash rates depend on a clear understanding of the factors that contribute to driver risk. Not all drivers are at equivalent risk. It is critical to identify the factors that contribute to the development of expertise in the driving environment. The rapid development of a driver's situation awareness (SA) is central to the safe performance of the driving task. Therefore, SA must be clearly operationalised in order to better assess its role in the development of expertise. This study employs an existing scheme based on the Perceptual Cycle Model (PCM) used for post hoc incident analysis and adapts it to the driving context. We attempted to correlate performance on coded verbalisations indicative of SA with non-invasive objective gaze metrics. Gaze metrics and the verbal counts were shown to differentiate between both expert and experienced (non-expert) drivers, but these measures failed to correlate with one another. Findings indicate differences in the way expert and experienced drivers update their schema of the driving task, with equivalent effort required to do so. The novel adaptation demonstrated in this paper allows for a domain-specific assessment of SA which reliably differentiates between drivers of varying expertise levels. Although selected gaze metrics were shown to be inadequate predictors of SA, additional analysis demonstrated key differences in gaze content. Combined, these findings enhance an understanding of expert SA development contributing to reduced crash risk.